1986
DOI: 10.1111/j.1530-0277.1986.tb05070.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol Exposure during the Third Trimester Equivalent on Neuron Number in Rat Hippocampus and Dentate Gyrus

Abstract: An artificial rearing procedure was used to expose neonatal rats to a formula containing 3.74% ethanol during postnatal days 4 through 10. This treatment produced a mean blood ethanol concentration of 379.8 +/- 17.3 mg/dl. When the pups were killed on the afternoon of postnatal day 10, brain weight to body weight ratio in the ethanol-exposed rats was reduced 22.4% and 21.5% compared to suckle and pair-fed controls, respectively. Ethanol exposure also resulted in a 16% reduction of neurons in hippocampal field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(60 citation statements)
references
References 36 publications
5
54
0
1
Order By: Relevance
“…Although ethanol appears to affect proliferation in some populations [Miller, 1986], in many studies it has been shown to exert the most damaging effects in later periods, during stages of neuronal maturation and differentiation [Goodlett and Eilers, 1997;West et al, 1994West et al, , 1986. In addition, in the chick embryo, as noted earlier, we have found that ethanol applied during a period well after the completion of proliferation within this population (G10-15; motoneuron generation occurs from G2-5 [Hollyday and Hamburger, 1977]) also results in motoneuron loss [Bradley et al, 1997[Bradley et al, , 1999.…”
Section: B Asupporting
confidence: 49%
See 1 more Smart Citation
“…Although ethanol appears to affect proliferation in some populations [Miller, 1986], in many studies it has been shown to exert the most damaging effects in later periods, during stages of neuronal maturation and differentiation [Goodlett and Eilers, 1997;West et al, 1994West et al, , 1986. In addition, in the chick embryo, as noted earlier, we have found that ethanol applied during a period well after the completion of proliferation within this population (G10-15; motoneuron generation occurs from G2-5 [Hollyday and Hamburger, 1977]) also results in motoneuron loss [Bradley et al, 1997[Bradley et al, , 1999.…”
Section: B Asupporting
confidence: 49%
“…Such deficits have been described in a great many regions and structures of the developing mammalian brain and brainstem, including the cerebral cortex [Miller, 1986], hippocampus [Barnes and Walker, 1981;West et al, 1986], cerebellum [Hamre and West, 1993;Pierce et al, 1993;Goodlett and Eilers, 1997], substantia nigra [Shetty et al, 1993], red nucleus [Zajac et al, 1989], inferior olivary nucleus [Napper and West, 1995], basal ganglia [Heaton et al, 1996;Mattson et al, 1994], olfactory bulb [Bonthius and West, 1991;Bonthius et al, 1992], optic nerve [Ashwell and Zhang, 1994], corpus callosum [Riley et al, 1995], chief sensory trigeminal nucleus [Miller and Muller, 1988] and the oculomotor nucleus [Burrows et al, 1995]. Very little information is available concerning ethanol effects on neurological structures caudal to the brainstem, however.…”
Section: Introductionmentioning
confidence: 99%
“…Details of alterations in CNS structure and function caused by ethanol exposure during development have been reported to occur in both humans and laboratory animals (e.g., Hammer and Scheibel, 1981;Riley et al, 1986;Streissguth, 1986;West et al, 1986;Miller and Muller, 1989;Miller and Potempa, 1990;Driscoll et al, 1990;Phillips and Krueger 1992;Pauli et al, 1995a;Dangata and Kaufman, 1997;Miki et al, 1999;Maier and West, 2001). Animal studies that have used the rat as a model have often carried out ethanol exposure during about the first 10 -14 postnatal days (PND) of life.…”
Section: Introductionmentioning
confidence: 97%
“…Most studies on the effects of alcohol on brain development have focused on the third-trimester model. For example, early studies from West and his colleagues used a third-trimester model in rats to demonstrate neuronal cell loss in the cerebellum, olfactory bulb, and hippocampus after alcohol exposure (12)(13)(14)(15)(16)(17). Rodent cell culture models and tumor-derived cell lines also have been used extensively to understand the effects of ethanol on neuronal survival and differentiation, i.e., events that occur during the third trimester.…”
Section: Effects Of Alcohol During Brain Growth and Developmentmentioning
confidence: 99%